Global Governance in Question: Empire, Class and the New Common Sense in Managing North-South Relations - Baragar, Fletcher (Labour / Le Travail, 2008)
The article reviews the book, "Global Governance in Question: Empire, Class and the New Common Sense in Managing North-South Relations," by Susanne Soederberg.
Keywords: BOOKS – Reviews; GLOBAL Governance in Question: Empire; Class & the New Common Sense in Managing North-South Relations (Book); International relations; Nonfiction; SOEDERBERG; Susanne